A comparison of socioeconomic determinants that influence justification of physical violence against women in the Philippines 2013 and 2017 - Carlos, Andrea Bianca E.
This study examines which socioeconomic factors of both women and their partners affect their justification of physical violence against women in the Philippines in 2013 and 2017. Data from the 2013 and 2017 National Health Demographic Surveys were collected and respondents consist of never-married and ever-married women. In the survey, the female respondents were asked the question whether or not they justify acts of physical violence based on specific scenarios and their experience of violence committed by anyone and by their current or former partners. Answers were quantified with “yes” or “no”. Multiple linear regression models were used to analyze the relevance of the respondent’s age, partner’s age, respondent’s educational attainment, partner’s educational attainment, respondent’s religion, and their combined wealth index on the respondent’s justification of physical violence against women. The models demonstrated that factors associated with the respondent’s education, religious associations, and wealth index have a bearing on their justification of domestic abuse for both 2013 and 2017. The analysis suggests that women who have received a higher level of education are less likely to excuse violent acts of their partners. The same observation was made for respondents who belong to a higher wealth index. However, findings suggest that respondents who religiously identify as Roman Catholic or Islam have tendencies of providing rationale for physical violence against women.